The Effect of Brand Image and Product Design on Consumer Purchase Interest in Kriss Batik Products - Hadita Hadita; Dovina Navanti (Dinasti International Journal of Education Management And Social Science, 2025)
The study aims to determine the relationship between brand image variables and product design on consumer buying interest in Kriss Batik products. the sample used was 45 people. The results showed that the Brand Image Variable (Brand 1mage) (X1) had a significant effect on Consumer Purchase Interest (Y), from the results of data processing above that t count for each variable X1 2.238> t table 2.018 and significance value <0.05. The Product Design variable (X2) has a significant effect on Consumer Purchase Interest (Y), from the results of the data processing above that the t count of each X2 variable is 5.769> t table 2.018 and the significance value is <0.05. Likewise, all independent variables, namely Brand Image (X1) and Product Design (X2) together have an effect on Consumer Purchase Interest (Y), from the results of the data processing above that X1 and X2 produce a value of 0.000 <0.05, so it can be said that X1 and X2 have an effect on the independent variable.